If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -8x = 6 + -7x + 2x Combine like terms: -7x + 2x = -5x 6 + -8x = 6 + -5x Add '-6' to each side of the equation. 6 + -6 + -8x = 6 + -6 + -5x Combine like terms: 6 + -6 = 0 0 + -8x = 6 + -6 + -5x -8x = 6 + -6 + -5x Combine like terms: 6 + -6 = 0 -8x = 0 + -5x -8x = -5x Solving -8x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -8x + 5x = -5x + 5x Combine like terms: -8x + 5x = -3x -3x = -5x + 5x Combine like terms: -5x + 5x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| -5x-9y=1 | | -2x-3y=-74 | | 5x+23=2(11x+27) | | 11x^2+5x-18=0 | | X+5=1x | | 60n=45 | | 18x+8y=60whatisy | | 8x=666 | | 5x+5y=-40 | | (3w-4)(7+w)=0 | | 6y+15=39 | | 5n=3n+14 | | 8x+13y=-74 | | 6x-(2x+1)=1 | | 3x+13=8x+48 | | (x+5)-2(4-3x)=2(x+3)-4 | | 7c-63=22c-72 | | 1100-x=550 | | x*2+y*2=49 | | 2x^2+24x+50=0 | | (z+9)(3z+4)=0 | | 2b+7=4b+2 | | 15+4x=6+7x | | -2(-b-4)=-(b-8) | | 8.7x+4.42=-11.3x+3.18 | | 6+4w=13+3w | | -8(x+7)+5=-51 | | 4r+6=13+2r | | x*2+4*x+y*2-21=0 | | ln(4x^6+2x^3)=y | | 180=120x | | -2(b-4)=-(b-8) |